Pengaruh Permainan Edukasi “Puzzlo Puzzle” Terhadap Peningkatan Kemampuan Motorik Halus dan Kognitif Anak Usia 4-5 Tahun - Lavenia Elizya STT; Krisni Subandijah; Mergy Gayatri (Institut Nalanda, 2023)
. Stimulation plays a crucial role in maximizing the growth and development of children by targeting their specific age-related cognitive and fine motor skills. This study aims to investigate the effectiveness of the educational toy